Exploring the Role of Internal Audit: A Qualitative Study of Institutions in the Philippines: - Orencia, Abrian Joy (Future Science / FSH-PH Publications, 2023)
This qualitative study delved into the complex role of internal audit practices in various Philippine institutions. The research aimed to illuminate the qualitative aspects shaping internal audit's importance. Ten participants from governmental bodies, private corporations, non-profits, and financial institutions were interviewed, providing insights into their experiences and challenges. The findings emphasized internal audit's pivotal contribution to transparency, accountability, risk analysis, and overall organizational effectiveness. Despite its importance, institutions faced challenges such as limited resources, hierarchical barriers, and the need for continuous professional development of auditors. Key qualitative themes emerged, highlighting internal audit's role in promoting organizational integrity and effectiveness. The study acknowledged its limitations but underscored the importance of strategic investments to overcome challenges. It suggested reorienting internal audit as a strategic asset integrated into decision-making processes. Recommendations included adequate resource allocation, fostering collaborative cultures, strategic risk analysis, continuous professional development, incorporating audit insights into decisions, and aligning practices with institutional culture. This study provided a nuanced understanding of internal audit's evolving role in the Philippine context. Its insights offer valuable guidance for enhancing internal audit practices across diverse institutions, bridging theoretical concepts with practical applications.